The Lyme disease bacterium, Borrelia burgdorferi, stimulates an inflammatory response in human choroid plexus epithelial cells. - Derick Thompson; Jordyn Sorenson; Jacob Greenmyer; Catherine A Brissette; John A Watt (PLoS ONE)
The main functions of the choroid plexus (CP) are the production of cerebral spinal fluid (CSF), the formation of the blood-CSF barrier, and regulation of immune response. This barrier allows for the exchange of specific nutrients, waste, and peripheral immune cells between the blood stream and CSF. Borrelia burgdorferi (Bb), the causative bacteria of Lyme disease, is associated with neurological complications including meningitis-indeed, Bb has been isolated from the CSF of patients. While it is accepted that B. burgdorferi can enter the central nervous system (CNS) of patients, it is unknown how the bacteria crosses this barrier and how the pathogenesis of the disease leads to the observed symptoms in patients. We hypothesize that during infection Borrelia burgdorferi will induce an immune response conducive to the chemotaxis of immune cells and subsequently lead to a pro-inflammatory state with the CNS parenchyma. Primary human choroid plexus epithelial cells were grown in culture and infected with B. burgdorferi strain B31 MI-16 for 48 hours. RNA was isolated and used for RNA sequencing and RT-qPCR validation. Secreted proteins in the supernatant were analyzed via ELISA. Transcriptome analysis based on RNA sequencing determined a total of 160 upregulated genes and 98 downregulated genes. Pathway and biological process analysis determined a significant upregulation in immune and inflammatory genes specifically in chemokine and interferon related pathways. Further analysis revealed downregulation in genes related to cell to cell junctions including tight and adherens junctions. These results were validated via RT-qPCR. Protein analysis of secreted factors showed an increase in inflammatory chemokines, corresponding to our transcriptome analysis. These data further demonstrate the role of the CP in the modulation of the immune response in a disease state and give insight into the mechanisms by which Borrelia burgdorferi may disseminate into, and act upon, the CNS. Future experiments aim to detail the impact of B. burgdorferi on the blood-CSF-barrier (BCSFB) integrity and inflammatory response within animal models.